Protocol for assessing whether cognition of preterm infants <29 weeks' gestation can be improved by an intervention with the omega-3 long-chain polyunsaturated fatty acid docosahexaenoic acid (DHA): a follow-up of a randomised controlled trial. Issue 2 (5th February 2021) - Gould, Jacqueline F; Makrides, Maria; Sullivan, Thomas R; Anderson, Peter J; Gibson, Robert A; Best, Karen P; McPhee, Andrew J; Doyle, Lex William; Opie, Gillian; Travadi, Javeed; Cheong, Jeanie; Davis, Peter G; et al.
Abstract : Introduction: Docosahexaenoic acid (DHA) is an omega-3 (n-3) fatty acid that accumulates into neural tissue during the last trimester of pregnancy, as the fetal brain is undergoing a growth spurt. Infants born <29 weeks' gestation are deprived the normal in utero supply of DHA during this period of rapid brain development. Insufficient dietary DHA postnatally may contribute to the cognitive impairments common among this population. This follow-up of the N-3 fatty acids for improvement in respiratory outcomes (N3RO) randomised controlled trial aims to determine if enteral DHA supplementation in infants born <29 weeks' gestation during the first months of life improves cognitive development at 5 years of age corrected for prematurity. Methods and analysis: N3RO was a randomised controlled trial of enteral DHA supplementation (60 mg/kg/day) or a control emulsion (without DHA) in 1273 infants born <29 weeks' gestation to determine the effect on bronchopulmonary dysplasia (BPD). We showed that DHA supplementation did not reduce the risk of BPD and may have increased the risk. In this follow-up at 5 years' corrected age, a predefined subset (n=655) of children from five Australian sites will be invited to attend a cognitive assessment with a psychologist. Children will be administered the Wechsler Preschool and Primary Scale of Intelligence (fourth edition) and a measure of inhibitory control (fruit stroop), while height, weight and head circumference will be measured. The primary outcome is full-scale IQ. To ensure 90% power, a minimum of 592 children are needed to detect a four-point difference in IQ between the groups. Research personnel and families remain blinded to group assignment. Ethics and dissemination: The Women's and Children Health Network Human Research Ethics Committee reviewed and approved the study (HREC/17/WCHN/187). Caregivers will give informed consent prior to taking part in this follow-up study. Findings of this study will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: ACTRN12612000503820.